2009
DOI: 10.1007/s00213-009-1539-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous anhedonia and exaggerated locomotor activation in an animal model of depression

Abstract: These paradoxical findings are not consistent with the notion that reward and locomotion are mediated by a common substrate; this dissociation may be useful in modeling psychiatric disorders such as mixed depressive states. In addition, our findings suggest that central reward circuitry may constitute a possible target for rationally designed therapeutics for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 57 publications
9
20
1
Order By: Relevance
“…An exaggeration of locomotor activity in OBX animals was observed compared with sham rats when placed in a high illuminated open-field ( Figure 6). This is consistent with previous reports and is believed to be due to a deficit of habituation to a new stressful environment (Cairncross et al 1979;Van Riezen and Leonard, 1990;McNish and Davis, 1997;Song and Leonard, 2005;Romeas et al, 2009). Importantly, although fluoxetine was ineffective after a 7-day treatment (as expected for an SSRI; Lucas et al, 2007;Breuer et al, 2007), SB-269970 reversed the OBXinduced hyperactivity.…”
Section: Discussionsupporting
confidence: 92%
“…An exaggeration of locomotor activity in OBX animals was observed compared with sham rats when placed in a high illuminated open-field ( Figure 6). This is consistent with previous reports and is believed to be due to a deficit of habituation to a new stressful environment (Cairncross et al 1979;Van Riezen and Leonard, 1990;McNish and Davis, 1997;Song and Leonard, 2005;Romeas et al, 2009). Importantly, although fluoxetine was ineffective after a 7-day treatment (as expected for an SSRI; Lucas et al, 2007;Breuer et al, 2007), SB-269970 reversed the OBXinduced hyperactivity.…”
Section: Discussionsupporting
confidence: 92%
“…This behavioral paradigm is based on the discovery by Olds and Milner that rats will repeatedly press a lever to stimulate specific components of the brain reward circuit (Olds and Milner 1954). A number of studies have confirmed the validity of this technique for the assessment of both the rewarding and the anhedonic effects of drugs or other manipulations (Benaliouad et al 2007;Gallo et al 2010;Kornetsky 1985;Markou and Koob 1991;Morissette and Boye 2008;Paterson et al 2000;Romeas et al 2009;Slattery et al 2007;Wise 1996). Most drugs of abuse are able to lower the brain stimulation reward threshold, an effect which supports the notion that they activate the same substrate with electrical stimulation in a synergistic manner (Wise 1996(Wise , 1998.…”
Section: Introductionmentioning
confidence: 96%
“…This may be one explanation for the uncommon constellation of behaviours observed in our study. However, recently, a cooccurrence of behavioural activation after stress-induced anhedonia has been documented by others [100,101] and warrants further exploration. Selection for phenotypic variation in exploratory activity produced no major interactions with chronic stress; however, LE rats were somewhat more strongly affected by CVS in their weight gain and differed in their second-day FST behaviour.…”
Section: Discussionmentioning
confidence: 99%